Biomonitoraggio e determinazione delle emissioni inquinanti di NOx tramite licheni - Bellocchi, Daniele; Battellocchi, Giuseppe; Monachino, Chiara; Nardini, Stefanella; Guidobaldi, Elena; Baiocchi, Antonella; Billi, Luciana; Caprasecca, Elisa; Forti, Gianluca; Lisi, Antonella (Chimica nella Scuola, 2023)
Lichen diversity is a good indicator of air quality and health risk and there is a strong correlation between lichen diversity and lung disease like cancer and asthma. Biological monitoring by means of lichens is a very suitable tool to assess and monitor air pollution and it has been adopted in several surveys in Italy in the last 30 years. In our school, we try to implement the traditional air pollution monitoring with an innovative – self made - analysis that is based on Kjeldahl method of nitrogen analysis for the determination of total nitrogen uptake by Evernia prunastri to quantify the air pollution. The aim of this work is to assess the nitrogen oxides (NOx) pollution in the territory of Acquapendente and to give a boost to the municipal administration and scientific community’s efforts to permanently use lichens as bioindicators and bioaccumulators in territory of north Tuscia.